Antibody-mediated rejection-treatment standard - Böhmig, Georg A; Naesens, Maarten; Viklicky, Ondrej; Thaunat, Olivier; Diebold, Matthias; Rostaing, Lionel; Budde, Klemens (Nephrology, dialysis, transplantation, 2025)
Antibody-mediated rejection (AMR) remains a major cause of graft failure, with significant health and economic burden. Despite being recognized >25 years ago, AMR treatment remains unstandardized, and no therapy has gained robust regulatory approval. While uncontrolled series have shown promise, few well-designed trials exist, with most yielding negative results. In the absence of strong trial data, a Transplantation Society expert consensus recommended potential treatment options with low levels of evidence, tailored to clinical phenotypes. Here, we re-evaluate the current evidence for AMR treatment decisions. We conclude that steroids, rituximab, bortezomib, and interleukin-6 (IL-6) antagonists lack sufficiently robust evidence to support their use in AMR. For early AMR, antibody depletion using immunoadsorption could be considered as an alternative to plasmapheresis. High-dose intravenous immunoglobulin (IVIG) may be added, though the supporting evidence remains limited. While previous trials primarily targeted the cause of AMR, recent data on the successful reversal of AMR activity by CD38 antibodies-particularly recent phase 2 trial results-suggest that targeting the cellular inflammation resulting from antibody binding to the endothelium could be a rational approach. Along these lines, in severe early AMR, complement inhibition may also be an option. Ongoing phase 2 trials evaluating prolonged courses of high-dose IVIG, the neonatal Fc receptor blocker efgartigimod, the tyrosine kinase inhibitor fostamatinib, and the complement inhibitor BIVV020, along with phase 3 trials of the anti-IL-6 receptor antibody tocilizumab and the CD38 antibody felzartamab, offer hope for effective, approved therapies targeting different aspects of AMR pathobiology.
Keywords: Humans; Kidney Transplantation; transplantace ledvin; Graft Rejection; donor-specific antibody; CD38; apheresis; antibody-mediated rejection; lidé; rejekce štěpu; natural killer cells